Female geriatric patients with traumatic brain injury have better odds of survival compared to men-a meta-analysis and review of the literature - Pandya, Shreya; Fedoriv, Ivan; Le, Timothy N.; Liu, Jacqueline; Singer, Tori; Kennedy, Kaitlyn; Singer, Kiara; Lee, Bryan; Kaykaty, Vincent; Butler, Kevin; Singh, Kailey; Patel, Nikhil; et al. (International Surgery Journal, 2022)
Geriatric trauma patients have worse outcomes compared to younger patients. Differences in trauma outcomes based on gender remain unproven. We sought to investigate the association of gender with outcomes among geriatric patients with traumatic brain injury (TBI) by performing a meta-analysis and review of the literature. A systematic review of published articles on outcomes of geriatric patients with TBI using PubMed was conducted. A total of 363 articles were identified, from these, 74 articles met the inclusion criteria of isolated TBI in geriatric patients. Upon review of the articles, only 5 met the specified criteria of the search which described male and female mortality amongst geriatric patients suffering isolated TBI. The data from these papers were combined into a master file and meta-analysis was performed using random-effect model with Rev Man 5.4 software. The total number of patients in these 5 papers was 23,893, of these 11,971 were men and 11,922 were women. The odds ratio for survival in these patients were 1.40, 2.40, 1.20, 1.28 and 1.15 with a combined final OR of 1.28 favoring women with a p value of less than 0.00001 and CI of 1.21-1.36. Female geriatric trauma patients sustaining TBI have better survival than men.